2018
DOI: 10.2147/ndt.s151920
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma and dissociation among women with genito-pelvic pain/penetration disorder

Abstract: ObjectiveCauses such as childhood trauma, negative attitude about sexuality, inadequate sexual knowledge and education, relationship problems, and unconscious motivation are reported about psychosexual development in the etiology of genito-pelvic pain/penetration disorder (GPP/PD). There are few studies that focus directly on research etiology of GPP/PD and use structured scales. The aim of this study was to research childhood trauma and dissociation forms among women with GPP/PD.Patients and methodsFifty-five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
(66 reference statements)
0
9
0
3
Order By: Relevance
“…Recently, Farina et al (36) conceptualized dyspareunia as a somatoform dissociative symptom and found an odds ratio of 6.15 of psychoform dissociation in women with dyspareunia. Similarly, Özen et al (37) found high rates of somatoform dissociation in dyspareunia patients. Our study corroborates these data and is, to our knowledge, the first study specifically assessing perinatal dissociation in women with dyspareunia.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, Farina et al (36) conceptualized dyspareunia as a somatoform dissociative symptom and found an odds ratio of 6.15 of psychoform dissociation in women with dyspareunia. Similarly, Özen et al (37) found high rates of somatoform dissociation in dyspareunia patients. Our study corroborates these data and is, to our knowledge, the first study specifically assessing perinatal dissociation in women with dyspareunia.…”
Section: Discussionmentioning
confidence: 85%
“…A educação sexual inadequada contribui para expectativas sexuais irreais, relativas a como, a quando e ao que deve acontecer em uma relação sexual, sendo esse um dos principais motivos pelos quais os indivíduos enfrentam problemas sexuais (Vaishnav et al, 2020). Em relação às disfunções sexuais, o vaginismo possui etiologia desconhecida (Pacik, 2014;Batista, 2017), entretanto, estudos mostram correlações com a presença de crenças disfuncionais e atitudes negativas em relação ao sexo, aversão à genitália, restrita educação familiar e religiosa, estigmas culturais e familiares, medo da (primeira) penetração, virgindade, medo de engravidar, sexo só depois do casamento, ansiedade e medo ante a possibilidade de dor e a realização de exames ginecológicos, e ausência ou inadequada educação sexual (Alizadeh et al, 2019;Fadul et al, 2018;Özen et al, 2018;Pacik, 2014;Rahman, 2018;Vaishnav et al, 2020).…”
Section: Educação Sexualunclassified
“…A maioria desses autores também considerou traumas no desenvolvimento infantil, como abuso sexual (Özen et al, 2018;Pacik, 2014;Rahman, 2018;Vaishnav et al, 2020). No entanto, Fadul et al (2018) analisaram que a maioria dos estudos que consideram esse histórico não possui dados estatisticamente signifi- 2014).…”
Section: Educação Sexualunclassified
See 1 more Smart Citation
“…As a result, dissociative disorders occur. 3 , 4 Only 3% of the diagnosed patients are under 12 years old, and 8% are aged between 12 and 19. 5 There are many advantages of early detection and accurate diagnosis.…”
Section: Introductionmentioning
confidence: 99%